Temporal distribution, reproductive synchrony, and mating patterns of the explosive breeder frog Dermatonotus muelleri (Anura: Microhylidae) - Nomura, Fausto (2022)
The knowledge about natural history of a species is fundamental for the proposition of theories in population, community, and behavioral ecology. Dermatonotus muelleri (Boettger, 1885) is one of the several Neotropical anuran species that still lacks basic information. These frogs are widely distributed in South America and present many peculiar morphological features, such as a reduced head size and a tongue morphology that suggests a specialized diet in ants and termites. However, D. muelleri is rare in anuran surveys, because of the explosive breeding behavior, which restrict its occurrence in aquatic habitats to few days a year, and the semi-fossorial habit, making the individuals inactive during most part of the year. In this study, we describe the reproductive ecology of Dermatonotus muelleri, with special attention to the mechanisms that regulates (i) the reproductive synchrony between males and females and (ii) the operational sex ratio (OSR), and (iii) if size is a good predictor of pairs formation (assortative mating).